Sol-gel synthesis of mesoporous CaCu3Ti4O12 thin films and their gas sensing response - Parra, R.; Savu, R. [UNESP]; Ramajo, L. A.; Ponce, M. A.; Varela, José Arana [UNESP]; Castro, M. S.; Bueno, Paulo Roberto [UNESP]; Joanni, E. [UNESP] (Academic Press Inc. Elsevier B.V., 2010)
A new sol-gel synthesis procedure of stable calcium copper titanate (CaCu3Ti4O12-CCTO) precursor sols for the fabrication of porous films was developed The composition of the sot was selected in order to avoid the precipitation of undesired phases, ethanol was used as solvent, acetic acid as modifier and poly(ethyleneglycol) as a linker agent Films deposited by spin-coating onto oxidized silicon substrates were annealed at 700 degrees C The main phase present in the samples, as detected by X-ray diffraction and Raman spectroscopy, was CaCu3Ti4O12 Scanning electron microscopy analysis showed that mesoporous structures, with thicknesses between 200 and 400 nm, were developed as a result of the processing conditions The films were tested regarding their sensibility towards oxygen and nitrogen at atmospheric pressure using working temperatures from 200 to 290 degrees C. The samples exhibited n-type conductivity, high sensitivity and short response times. These characteristics indicate that CCTO mesoporous structures obtained by sol-gel are suitable for application in gas sensing (C) 2010 Elsevier Inc All rights reserved
Keywords: CaCu3Ti4O12; Mesoporous films; Gas sensors